Japanese contribution to Islamic studies : the legacy of Toshihiko Izutsu interpreted - Wok, Saodah (Public Relations Office, International Islamic University Malaysia, 2011)
The book is a compilation of 19 selected papers and essays transpired from a 3 days conference on The International Conference on Contemporary Scholarship on Islam : Japanese Contribution to islamic Studies - The Legacy of Toshihiko Izutsu (ICONSIST) 2008 at Kuala Lumpur. The chapters cover different issues and topics from various approaches related to Izutsu's remarkable work, ranging from Buddhist/Shinto views of the Islamic worldview, philosophy, mysticism/Sufism, semantic, linguistics and ethics to scientific study of religion. Professor Toshihiko Izutsu (1914-1993) was a scholar of Islam in japanese-Muslim relations. the book is available collection to understand Islam from thinking of an Eastern philosopher.